Evaluation of the Context of the Implementation of the Development Program for Five New Regional General Hospitals (RSUD) in Bandung Regency - Fadilla, Rizal Ahmad; Pancasilawan, Ramadhan; Darto (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2026)
This study evaluates the development program of five Type D Regional Public Hospitals (RSUD) in Bandung Regency using the CIPP (Context, Input, Process, Product) evaluation model. The study employs a qualitative approach with data collected through interviews, observations, and document analysis. A total of [isi jumlah, misalnya: 12] informants were selected using purposive sampling, including officials from the Health Office, hospital management, and community representatives. Data were analyzed using thematic analysis and mapped into CIPP dimensions. The findings indicate that, from a contextual perspective, the program has strong legal legitimacy and high urgency due to the low hospital bed ratio (0.52 per 1,000 population). However, input evaluation reveals constraints in human resources, particularly the shortage of specialist doctors. From the process dimension, delays in the construction of three hospitals are associated with bureaucratic complexity and coordination issues. Meanwhile, product evaluation shows initial improvements in healthcare access, although service performance indicators remain suboptimal. This study contributes to the literature by providing a decision-oriented evaluation of regional health infrastructure development and highlighting the importance of aligning resource planning, governance, and service outcomes in decentralized health systems.